Petroleum-fuelled methanogenesis and microbial hydrocarbon oxidation at an abandoned oil well - Martin Blumenberg; Sebastian Jordan; Georg Scheeder; Martin Krüger; Stefan Schloemer (Applied Geochemistry, 2025)

Abundance of phytanyl and n-alkyl toluenes in petroleum from the Lower Saxony Basin (Germany) provides information on maturity, palaeosettings and sources - Georg Scheeder; Christian Ostertag-Henning; Martin Blumenberg (Organic Geochemistry, 2025)

Rapidly changing environmental conditions in a coastal setting during the Berriasian (“German Wealden”, lower Cretaceous): evidence from biomarker and bulk geochemical data - Martin Blumenberg; Georg Scheeder; Fritz-Lukas Stoepke; Roberto Pierau; Jochen Erbacher (International Journal of Earth Sciences, 2025)
During the Middle to Late Berriasian (so called “German Wealden”) a large lake system developed in the Lower Saxony Basin (LSB; in northwestern Germany) of which the eastern part is characterized by varying fluvial and lacustrine influences. The changeable situation through the earliest Cretaceous, particularly in the eastern LSB, is relatively understudied and a recently drilled well (KB-Rehburg 2; R-2) can help shedding light on these variations. R-2 covers the Berriasian ostracod zones Wealden 1 to 4 (Wd1 to Wd4), and palynomorphs presented in another study record stages with fluctuating predominantly terrigenous or aquatic organic matter. Short-term marine ingressions (MI) and more extensive transgressive events (TE) during that time interval have been reported, but some remained questionable. We here present novel organic geochemical data (including Rock–Eval and biomarkers) from R-2 showing a low maturity in terms of organic geochemical stress (Rock–Eval T max ~ 435 to 445 °C) and bulk geochemical and biomarker data support the fluctuation in the sources of the predominating organic matter. In addition to the recently published marine influx events recorded in R-2, a significant decrease in pristane/phytane and increase in dinosterane index biomarker ratios demonstrate the previously unclear TE2 at the beginning of zone Wd4. While dinoflagellate cysts during that stage were reported to occur only sporadic, the dinoflagellate-specific dinosterane biomarker became highly abundant [“dinosterane/(regular steranes + dinosteranes)” ratio up to 0.15]. It demonstrates that dinoflagellates also flourished at R-2 during zone Wd4. This palynomorph/biomarker mismatch may be explained by the prevalence of non-cyst forming, or less likely, non-preservation of cells of dinoflagellates. Our data from R-2 also points at a likely widespread and general complication for palaeoreconstructions because we observed a slight lag between first records of palynomorphs used for TE and MI event identification compared to changing biomarker ratios and bulk organic geochemistry. We hypothesize that while the first likely demonstrate first occurrences of pioneer organisms, which mark events best, organic geochemical data appear to be more integrating and record changes only after establishment of a palaeoenvironment. Graphical Abstract

Palladium-doped and undoped polystyrene nanoplastics in a chronic toxicity test for higher plants: Impact on soil, plants and ammonium oxidizing bacteria - Martin Hoppe; Jan Köser; Georg Scheeder; Axel Lamparter; Kristof Dorau; Lena Grüger; Georg Dierkes; Karsten Schlich (NanoImpact, 2023)

Biomarker paleo-reconstruction of the German Wealden (Berriasian, Early Cretaceous) in the Lower Saxony Basin (LSB) - Martin Blumenberg; Klaus G. Zink; Georg Scheeder; Christian Ostertag-Henning; Jochen Erbacher (International Journal of Earth Sciences, 2019)

Organic-geochemical Differentiation of Petroleum-type Pollutants and Study of Their Fate in Danube Alluvial Sediments and Corresponding Water (Pančevo Oil Refinery, Serbia) - Branimir Jovančićević; Miroslav Vrvić; Jan Schwarzbauer; Hermann Wehner; Georg Scheeder; Dragomir Vitorović (Water, Air, & Soil Pollution, 2007)

Transformations of n -alkanes from petroleum pollutants in alluvial groundwaters - Branimir Jovancicevic; Predrag Polic; Miroslav Vrvic; Georg Scheeder; Manfred Teschner; Hermann Wehner (Environmental Chemistry Letters, 2003)